A Case of Synchronous Multiple Metastases in which the Origin Could Not Be Identified by Routine Examination - Fujiwara, Ryo (Hinyokika kiyo. Acta urologica Japonica, 2016)
A 67-year-old man presented at our hospital with severe edema on the left side of his neck, chest and brachial regions. He had a history of right radical nephrectomy due to renal cell carcinoma (RCC, clear cell subtype, stage II) 15 years earlier. Thereafter, metastases to the pancreatic tail and right lung, and left lung metastasis were removed at 8 years and 11 years, respectively, after the nephrectomy. Four years earlier, he had also undergone total gastrectomy for gastric carcinoma (poorly differentiated adenocarcinoma, stage IV) and subsequent maintenance chemotherapy for gastric carcinoma. Follow-up computed tomography (CT) disclosed bilateral lung metastases and a pancreatic head metastasis. Cytology of pleural effusion on admission suggested pleuritis carcinomatosa from RCC. Clinical diagnosis was bilateral lung and pancreatic head metastases, pleuritis carcinomatosa and left subclavian vein thrombosis due to RCC metastasis. Maintenance chemotherapy for gastric carcinoma was replaced by Sunitinib 50 mg for RCC but he died of progressive disease 20 days later. Immunohistochemical study of the tissue from autopsy revealed lung metastasis and pancreatic head metastasis from both RCC and gastric carcinoma as well as multiple visceral metastases, pleuritis carcinomatosa and left subclavian vein thrombosis due to gastric carcinoma. Cause of death was acute respiratory failure due to pulmonary tumor embolism and pulmonary edema. Immunohistochemical study from autopsy was able to reveal the exact diagnosis, and immunohistochemical studies may be helpful in diagnosing the exact origin of metastasis and selecting appropriate treatmentsin patientswith multiple cancers